Safety and Health Problems in the Small and Medium Scale Metal Fabrication Enterprises in Willowvale Industrial Area In Harare, Zimbabwe - Gwezuva, Norman; Jerie, Steven (2022)
The objectives of this study were to identify the types of small and medium scale metal fabricating enterprises operating in Willowvale and to assess the existing hazards in these enterprises so as to analyse the effectiveness of the occupational safety and health management practices being implemented. The study used both quantitative and qualitative approaches with the research subjects being selected using stratified random sampling and purposive sampling methods. Questionnaires, interviews, observations and occupational hygiene measurements were used in data collection. The analysis of the collected data through the use of SPSS version 11.5 and Microsoft Excel 2007 revealed that the majority of small and medium scale metal fabricating enterprises were operating outside the requirements of the Zimbabwean OSH laws and regulations by failing to have their premises registered under the Factories and Works Act. OSH management structures were virtually non-existent and the implementation of OSH programs was predictably poor and minimal. Employees were exposed to numerous workplace hazards in the form of excessive noise, heat stress, hazardous metal working chemicals, awkward work postures to name just but a few. In conclusion, several recommendations to improve the state of OSH in this economic sector were proposed. These included tailor made and deliberate interventions being required from the regulatory authorities where the main thrust of such interventions will be on awareness and training campaigns so as to develop and cultivate the necessary skills, knowledge and attitudes toward sustainable OSH practices in metal fabricating SMEs.